Experienced Learners from Generation Z and the Traditional Vision of the Good Language Teacher: On The Issue of Teacher Authenticity - Nosidlak, Katarzyna (Neofilolog, 2024)
Different societies have their own perspectives on the definition of a good language teacher, as their members attach varying degrees of importance to the different skills and personal qualities required for effective teaching. While available studies have identified numerous desired language and pedagogical competencies among educators, the dynamic post-pandemic reality has brought increased attention to the importance of building and maintaining relationships with students. This process inevitably involves emotional engagement from both educators and students. Consequently, there is a growing call for both groups to accept their true selves and act authentically in their educational interactions. In response to the promotion of these values in education, this article aims to present the results of a study that sought to examine how experienced language students, representing Generation Z in Poland, define and evaluate authentic behaviours of their foreign language teachers. The participants of the study were asked to complete an online questionnaire containing both open and closed questions about their perceptions of their teachers’ authenticity. The thematic analysis of the qualitative data revealed a one-sided, unequivocally positive perception of authenticity, both in the general sense and in relation to the educational context. Numerous positive traits, such as sincerity, openness, sense of humour and didactic expertise were recognised as characteristics of authentic language teachers.